De Kant a Kuhn, acotando por Putnam - Alvarez Alvarez, José Francisco (ENDOXA, 2004)
Our aim in this paper is to trace in some detall the deep influence of Kant's epistemology on T.S. Kuhn's model of scientific change, specially on the kind ofrealism this model presupposes. In order to do this, we highlight the hard core thesis of what H. Putnam (1981) has called «intemal realism» —a kind of kantian realism— and then we try to show the strong resemblance between these thesis and Kuhn's ontological commitments. Last, we point to some advantages this kantian perspective offers in the way to construct a more adequate notion of objectivity and rationality